Bifurcation analysis of a discrete-time prey-predator model - Naik, Parvaiz; Eskandari, Z.; Shahkari, Hossein Eskandari; Owolabi, Kolade M (Fırat Evirgen, 2023)
This paper investigates the importance of studying the dynamics of predator-prey systems and the specific significance of Neimark-Sacker and period-doubling bifurcations in discrete-time prey-predator models. By conducting a numerical bifurcation analysis and examining bifurcation diagrams and phase portraits, we present important results that differentiate our study from others in the field. Firstly, our analysis reveals the occurrence of Neimark-Sacker and period-doubling bifurcations in the model under certain parameter values. These bifurcations lead to the emergence of stable limit cycles characterized by complex and unpredictable dynamics. This finding emphasizes the inherent complexity and nonlinearity of predator-prey systems and contributes to a deeper understanding of their dynamics. Additionally, our study highlights the advantages and limitations of employing discrete-time models in population dynamics research. The use of discrete-time models allows for a more tractable analysis while still capturing significant aspects of ecological systems. In conclusion, this study holds importance in shedding light on the dynamics of predator-prey systems and the specific role of Neimark-Sacker and period-doubling bifurcations. Our findings contribute to the understanding of predator-prey systems and offer implications for ecological management strategies.
Keywords: Biological Mathematics; Biyolojik Matematik; Applied Mathematics (Other); Uygulamalı Matematik (Diğer)